2020
DOI: 10.1038/s41566-020-0657-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locked laser-wakefield electron acceleration

Abstract: Subluminal and superluminal light pulses have attracted a considerable attention in the past decades [1][2][3][4] opening perspectives in telecommunications, optical storage, and fundamental physics 5 . Usually achieved in matter, superluminal propagation has also been demonstrated in vacuum with quasi-Bessel beams 6, 7 or Spatio-Temporal Couplings 8, 9 (STCs). While in the first case the propagation was diffraction-free, but with hardly controllable pulse velocities and limited to moderate intensities, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 38 publications
(40 reference statements)
0
39
0
1
Order By: Relevance
“…In this case, the propagating time-dependent motions can be well controlled by carefully optimizing the shape of the pulse-front deformation, creating optical wave-packets with unusual motion forms. As regards applications, we believe it can be used in some propagating velocity matched experiments, such as bio-imaging, particle-manipulation, particle acceleration, and radiation generation [75][76][77] , and the high spatiotemporal controllability could also offer new opportunities for fundamental studies in optics and physics.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the propagating time-dependent motions can be well controlled by carefully optimizing the shape of the pulse-front deformation, creating optical wave-packets with unusual motion forms. As regards applications, we believe it can be used in some propagating velocity matched experiments, such as bio-imaging, particle-manipulation, particle acceleration, and radiation generation [75][76][77] , and the high spatiotemporal controllability could also offer new opportunities for fundamental studies in optics and physics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the challenge of producing stable long-distance channels [50], curved channel technology will provide a useful method to control the directionality of electron beams and laser pulses [51]. In addition, recent theoretical and numerical studies proposed to overcome the dephasing length of LWFA, so-called phase-locked [52] or dephasingless [53] LWFA, by adapting the superluminal velocity of focal spot movement [54], which can be a way to maximize electron energy for given laser power.…”
Section: Perspective Of Lwfa With Pw Lasersmentioning
confidence: 99%
“…However, some of these methods demand sophisticated configurations, and the produced e beams are deficient in charge, energy spread, or peak energy, which hinder their practical applications. Recently, some significant studies have been reported to improve the specific qualities of e beams, including the peak energy [16][17][18][19][20], the energy spread [21][22][23][24][25][26], the brightness [24,27,28], the reproducibility [29][30][31], etc. More considerable research efforts, however, are still needed to focus on generating reproducible high-quality electrons for table-top light sources, which should have a broad-ranging impact across multiple scientific fields.…”
Section: Introductionmentioning
confidence: 99%